Unique Packaging : Headbanger Lures - Nilsson, Erik (2016)
Headbanger Lures is a startup company from Luleå, Sweden that has a brand new design on fishing lures. The lures head is created to make irregular movements in the water which is ground breaking design for today’s fishing lure market.This thesis is directed towards the design of the package that the lure is sold in, with key interest in creating something different that would present the lure to the buyer in a special way. In the process of doing this the project also had a direction towards an extra function that could have been added to the package and by doing that giving the package a longer life span.The beginning of the project is focused on data collection: literature about package design and design basics, observations and interviews of primer and secondary users/design experts/environments/market/company/benchmarking. The data is gathered into an analysis that is used in development section of the project.By working with workshops and clustering 3x3 package solution are presented in the end of the ideation phase which is divided into three production cost groups: 5, 10 and 15 Swedish kronor. The company then chose two concepts and merged them into one which are then moved on with into the last phase of the project. The chosen concept is based on a smart choice of a cheaper solution that has a special opening function and is within the similar dimensions as the package that is used today.Implementation chapter is based on the iteration work in the prototype lab, it shows the different solutions that were designed and the two chosen concepts for the end result. The work with users continues here but with more of a usability direction than an expertise influence that the data collection contained. The users contribute with valuable information about the interaction with the package in different ways which then keeps the project turned in the right direction. Validerat; 20160628 (global_studentproject_submitter)